Structural Failure Models for Fault-Tolerant Distributed Computing - Warns, Timo.; SpringerLink (Online service) (Wiesbaden : Vieweg+Teubner, 2010)
Given that faults cannot be prevented in sufficiently complex systems, means of fault tolerance are essential for dependable distributed systems. Designing and evaluating fault-tolerant systems require well-conceived fault models. In the past, theoretical works have used simplified models that, while being tractable, turned out to be inaccurate. Practical works have used probabilistic fault models that, while being more accurate, often turned out to be intractable. Timo Warns bridges the gap between theory and practice regarding fault models. He has developed tractable fault models that, while being non-probabilistic, are accurate for dependent and propagating faults. Using seminal problems such as consensus and constructing coteries, he demonstrates how the new models can be used to design and evaluate effective and efficient means of fault tolerance.
Modelling Fault-Tolerant Distributed Systems -- Modelling Fault Assumptions with Structural Failure Models -- Constructing Coteries -- Reaching Consensus -- Conclusion and FutureWork.
Keywords: Computer science; Computer Science; Computer Science, general